The Myth of the Ecological Class: On the Embeddedness of Ecological Conflict in Social Class Antagonisms - Staab, Philipp; Dorschel, Robert (DIE ERDE – Journal of the Geographical Society of Berlin, 2026)
Climate change and ecological crises are not only impacting temperatures and environments but are also reshaping the political dynamics within late-modern societies. For decades, liberal democracies have predominantly relied on a combination of grassroots subpolitical self-organization from below and market-based techno-scientific governance from above as their primary response to ecological challenges. However, in recent years, the escalating crisis of planetary ecology has led to a growing chorus of voices, both within society and academia, advocating for new forms of politicizing ecological issues. Particularly noteworthy is the concept of ecological class, which has emerged in the context of debates that place ecological concerns at the forefront of political contention. We problematize the predominant theorization of ecological class developed by Latour and Schultz by scrutinizing its geographical and subjectivist conceptualization. We stress the need to capture multifaceted objective and subjective class positionings and highlight the inherently relational nature of all class conflict. Drawing upon data on ecological inequalities, we contend that the core dimensions of ecological class conflict are fundamentally rooted in social class antagonism. Thus, ecological classes are actually social classes.